Wegener Granulomatosis Revealed by Pleural Effusion - Anne-Claire Toffart; François Arbib; Sylvie Lantuejoul; Jean-François Roux; Vincent Bland; Gilbert Ferretti; Samia Diab (Case Reports in Medicine)
Pulmonary signs are common in Wegener's granulomatosis (WG). However, an initial presentation including pleural effusion has not been described. We describe a case of WG in which pleural effusion was the first clinical manifestation. A 45-year-old man with dorsal pain presented with pleural thickening and effusion, and a visible nodule on a thoracic scan. A dense chronic inflammatory infiltrate was obtained by pleural biopsy and an open lung biopsy revealed necrotizing granulomatous vasculitis. Serologies were positive for antineutrophil cytoplasmic antibodies and antiproteinase 3 antibodies. A diagnosis of WG was conducted and the patient was started on cyclophosphamide and methylprednisolone as an initial treatment, with a favorable evolution. Although pleural effusion is rarely described in WG, this pathology must be considered in the presence of this clinical manifestation.